Perceived working conditions of graduates between 2010 and 2020 of the Faculty of Physical Education, Recreation and Sports of the Colombian Polytechnic Jaime Isaza Cadavid (Impetus, 2025)
The main objective of the research reported in this article was to identify the working conditions of graduates between 2010 and 2020 of the Faculty of Physical Education, Recreation and Sports of the Colombian Polytechnic Jaime Isaza Cadavid, of the Bachelor's Degree programs in basic education with emphasis on physical education, recreation and sports and Professional in Sports. The focus of the research was mixed, not experimental with an exploratory scope, as it was intended to know the employment situation of the graduates in the different centers of action and to inquire about their conditions taking into account the types of hiring and the remuneration received for their professional services. The research information was collected through a Google form to have a greater reach of the Faculty's graduates between 2010 and 2020. From this data collection exercise, 178 responses were obtained, corresponding to 7.8% of the total graduate population. A categorical analysis was carried out that allowed the visualization of aspects that must be reinforced in the academic processes in order to improve skills and labor competencies in students so that they are competitive in the sector, which is increasingly demanding and with less supply.
Keywords: Working conditions; job performance; graduates